PERLINDUNGAN KEPADA PEMEGANG HAK CIPTA SINEMATOGRAFI TERHADAP PEMBAJAKAN FILM MELALUI APLIKASI TELEGRAM BERDASARKAN UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - Paulus Revel Gian Raditya Dheasaputra; Si Ngurah Ardhya; Komang Febrinayanti Dantes (Universitas Pendidikan Ganesha, 2023)
This research was prepared with the aim of knowing, analyzing and studying (1) the characteristics of piracy of cinematographic works, (2) law enforcement carried out against perpetrators of piracy of cinematographic works through the telegram application based on Law Number 28 of 2014 concerning Copyright and Singapore Copyright Act 2021, as well as (3) legal protection given to copyright holders against piracy of cinematographic works based on Law Number 28 of 2014 concerning Copyright and the Singapore Copyright Act 2021. In order to answer the problem formulation in this research, a normative legal research method was used, namely Research which was carried out by examining library materials and secondary data regarding analysis from a legal perspective of Law Number 28 of 2014 concerning Copyright and the Singapore Copyright Act 2021. Through this research method, results were obtained (1) that the characteristic of piracy of cinematographic works is the act of copying recording results without permission, as well as distribution to generate personal economic gain. (2) the lack of effective enforcement of the Copyright Law in Indonesia means that piracy is still widespread in Indonesia, and (3) related to the legal protection provided in the form of preventive and repressive measures that have the same set of rules